Synthesis of diverse nitrogen fused polycyclic dihydroisoquinoline (DHIQ) derivatives via GBB-based cyclic iminium induced double-annulation cascade - Balwe, Sandip Gangadhar; Vagh, Sandip S.; Jeong, Yeon Tae (Tetrahedron Letters, 2020)
A highly efficient and distinct Bronsted acid-mediated unprecedented cyclic iminium induced double annulation cascade (DAC) protocol for the synthesis of novel dihydroindazolo[30,20:2,3]imidazo[5,1-a]isoquinolinamines has been achieved through the three-component Groebke-Blackburn-Bienayme reaction. The transformation is based on sequential cascade processes involving imine formation followed by an intramolecular nucleophilic substitution to generate a highly reactive cyclic iminium species, which would undergo a rapid [4 + 1] formal cycloaddition steps in one-pot fashion. This strategy provides novel skeletally diverse complex nitrogen fused polycyclic DHIQ derivatives by employing readily available substrates and a simple procedure, which would render this method potentially useful in organic synthesis. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: diversity-oriented synthesis; Excellent yields; GBB-based approach; Novel polycyclic N-fused architecture; Scalable